2021
DOI: 10.1016/j.epsl.2021.116784
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of omphacite and garnet indicates limited deep water recycling by crust subduction

Abstract: It is usually stated that oceanic crust recycling at subduction zones introduces large quantities of water into Earth's interior. However, it remains clouded how much water is recycled to the deep mantle. This is largely due to the challenge in directly sampling, and analyzing the water content of, a deep subducting crust. The subducting crust below ~30 km depth is dominated by omphacite and garnet in eclogite-facies rocks. Here we have determined the electrical conductivity of omphacite and garnet in represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 50 publications
(141 reference statements)
9
25
0
Order By: Relevance
“…Although present at parts-per-million (ppm) levels in NAMs, water has a disproportionate effect on many physical and chemical properties of the host minerals, and on Earth's dynamics. Typically, water lowers melting temperature (Hirose and Kawamoto, 1995;Gaetani and Grove, 1998), promotes ionic diffusion (Hier-Majumder et al, 2005;Costa and Chakraborty, 2008), facilitates plastic deformation (Mackwell et al, 1985;Mei and Kohlstedt, 2000), and enhances electrical conductivity (Karato, 1990;Yang et al, 2011;Yang and McCammon, 2012;Zhang et al, 2012;Liu et al, 2021). Therefore, water in NAMs is key to understanding processes of the deep Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Although present at parts-per-million (ppm) levels in NAMs, water has a disproportionate effect on many physical and chemical properties of the host minerals, and on Earth's dynamics. Typically, water lowers melting temperature (Hirose and Kawamoto, 1995;Gaetani and Grove, 1998), promotes ionic diffusion (Hier-Majumder et al, 2005;Costa and Chakraborty, 2008), facilitates plastic deformation (Mackwell et al, 1985;Mei and Kohlstedt, 2000), and enhances electrical conductivity (Karato, 1990;Yang et al, 2011;Yang and McCammon, 2012;Zhang et al, 2012;Liu et al, 2021). Therefore, water in NAMs is key to understanding processes of the deep Earth.…”
Section: Introductionmentioning
confidence: 99%
“…hydrous olivine and its high-pressure polymorphs. This idea is also supported by the electrical conductivity of granulites [ 123 ], pyroxenites [ 124 ] and eclogites [ 125 , 126 ].…”
Section: Origin Of High-conductivity Anomalies In Earth’s Mantlementioning
confidence: 89%
“…As the dominant endmember of constituent mineral in gabbro, the mineralogical content of clinopyroxene has a significant influence on the electrical conductivity of the sample at conditions of 773-1073 K, 1.0 GPa and controlled oxygen fugacity by a Ni-NiO solid buffer. As displayed in Figure 9a, five previously reported results on the electrical conductivity of natural clinopyroxene were employed to compare it in detail [11][12][13][14][15]. Previous results have already confirmed that the iron content and water content are two crucial influential ingredients in the electrical conductivity of Fe-bearing silicate minerals at high temperatures and high pressures [25,[27][28][29][30].…”
Section: Comparisons With Previous Studiesmentioning
confidence: 92%
“…By virtue of the Wayne Kerr B642 alternating current analyzer at a fixed frequency of 1.6 kHz, electrical conductivities of natural and synthetic polycrystalline diopside were measured at temperatures of 913-1337 K and pressure of 1.0 GPa [13]. Liu et al [14] carried out the impedance spectroscopic measurements on omphacite single crystals containing 7.92 wt% iron and 0.0085 wt% water at temperatures of 623-973 K and 1.0 GPa in a piston-cylinder press. Sun et al [15] researched the electrical conductivities of the clinopyroxene-NaCl-H2O systems with various fluid fractions and salinities at 673-973 K and 1.0 GPa, and they found that the NaClbearing aqueous fluids in clinopyroxene can greatly enhance the electrical conductivity of fluid-bearing sample.…”
Section: Introductionmentioning
confidence: 99%